(untitled) (Journal of Partial Differential Equations, 1998)
We describe some recent results on solutions of the static, stationary, spherically symmetric solutions of the SU(z) Einstein-Yang/Mills equations. The main result is that any solution which is defined in the far field and has finite (ADM) mass, is defined for all r > 0.